Analysis of Grid Tied Solar Rooftop System: A Case Study on Stars Homes, Sitapaila, Nepal - Prajapat, Milana; RajPahar, Bharat; Shakya, Shree Raj (Journal of Advanced College of Engineering and Management, 2021)
Most of the nation demand is from the residential sector. Thus, the objective of this paper is to supply the required energy from the same demand point from the solar PV installed in the residential sector that is technically feasible for the given sector. The survey is conveyed on Star Homes(Residential Sector) situated at Sitapaila, Kathmandu. The total potential for installation of PV on useable areas of the rooftop of Stars Homes is calculated to be 253.2 kWp. For the comparative analysis in this paper, the isolated PV system is designed/ analysed using PV-SYST and the grid tied PV including/excluding battery is designed/analysed using SAM(System Advisory Model) software for one of the Type 1 home with annual demand of 2208 kWh. In grid interactive PV system with battery, the peak shaving and backup power during outage is facilitated and also the excess energy is supplied to the grid as well.Theenergy generated from the designed system for type I system with 3.9 kWp grid tied system is 6483 kWh and with 3.9 kWp grid interactive system with battery size of 5.2kWh Lithium Ion is 6454 kWh annually. Similarly, energy generated from designed system of standalone with 1.62 kWp PV and battery size26V, 322Ah system is 3066.6 kWhannually out of which 795kWh is lost annually due to full battery charged conditions. The LCOE considering 25 years life time with 7.5 % loan interest for 15 years for type I with standalone system is 21 cents/kWh, grid tied PV system is 4.94 cents/kWh and with grid tied PV battery system is 6.73 cents/kWh. The peak shaving obtained from the grid tied with battery system compared to the grid tied system is 0.8 kW. The net saving on electricity bill for grid tied system is 516 and for grid tied system with battery is 526 annually considering net metering.